1996
DOI: 10.1016/s0167-8922(08)70777-6
|View full text |Cite
|
Sign up to set email alerts
|

The Entrainment of Solid Particles into Rolling Elastohydrodynamic Contacts

Abstract: The entry of lubricant borne solid particles into machine element contacts is important, both for prediction of three body abrasive wear, and for an understanding of the behaviour of solid lubricant additives. This paper describes a quantitative study of particle entrainment into a rolling elastohydrodynamic contact. The level of surface indentation is used as an indication of the number of particles entrained into the contact. It is shown that over the range of test conditions considered; concentrations of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…Counting the number of surface dents on a rolling element has been used [2] to determine the proportion of particles in a lubricant supply that enter a contact. A simple ball on flat rolling contact was used with low levels of contamination with diamond particles (which would not fracture and so lead to multiple indentations).…”
Section: Indent Counting Experimentsmentioning
confidence: 99%
“…Counting the number of surface dents on a rolling element has been used [2] to determine the proportion of particles in a lubricant supply that enter a contact. A simple ball on flat rolling contact was used with low levels of contamination with diamond particles (which would not fracture and so lead to multiple indentations).…”
Section: Indent Counting Experimentsmentioning
confidence: 99%
“…The number of particles which take part in this material removal process must be estimated. Previous work [5] has shown that it is not safe to assume that the concentration of particles in the contact is the same as that in the bulk. Experimental data shows how the contact can have a particle concentrating effect which varies with particle size and contact speed.…”
Section: Number Of Particles Entering the Contactmentioning
confidence: 99%
“…The particle entry ratio φ is approached empirically. A separate study [5] has been carried out for this purpose. The apparatus consisted of a steel ball loaded onto a flat steel disk and run in pure rolling with a lubricant mixed with diamond particles of known size.…”
Section: Number Of Particles Entering the Contactmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of a dent on the EHL lubrication of a line or point contact was the subject of many investigations starting from late 70s, first experimentally [10][11][12][13] and later numerically [14][15][16]. Experimental and theoretical work on particle entrapment in the EHL conjunction, particle deformation and debris denting [17][18][19][20][21][22][23][24][25][26], and subsequent wear or fatigue life reduction [27][28][29][30][31][32][33][34][35][36][37][38] has then been a hot research topic and especially welcomed by leading bearing manufacturers and academia. The first attempts to quantify the effects of lubricant cleanliness on the fatigue life reduction are due to Tallian [27,28].…”
Section: Introductionmentioning
confidence: 99%